مجموعہ ہائےمکاتیب ِاقبال ( تحقیقی مطالعہ، نتائج و سفارشات) - Hafiz Saif Ullah; Dr. Muhammad Asif (Khayaban - خیابان, 2022)
In the perspective of literary and intellectual and documentary and valuable significance, the editors,kings,politicians and statesman have been not only on the search of the letters of the pundits of literature but also bringing those letters for the public reading in book forms by their untiring efforts. The compilation of letters of Iqbal is necessary because they cover approximately 39 years of his life. These letters of Iqbal are also important because they reveal the personality of a person who left durable efforts on religion, philosophy, literature and politics. Despite these facts the letters of Iqbal are not given so much importance as they deserve. The poetry of Iqbal can be interpreted in the light of these letters, so the intellectual and literary value of the letters of Iqbal demands that they not only be compiled once again but also the perspective and background of each letter be interpreted and explained.